HIV sexual risk behaviors and perception of risk among college students: implications for planning interventions - Balogun Joseph A; Abiona Titilayo C; Adefuye Adedeji S; Lukobo-Durrell Mainza (BMC, 2009)
Abstract Background The college environment offers great opportunity for HIV high-risk behaviors, including unsafe sex and multiple partnerships. While the overall incidence of HIV infection has seen some decline in recent years, rates of HIV infection among young adults have not seen a proportionate decline. As in the general population, African American young adults have been disproportionately affected by the HIV/AIDS epidemic. This study examined the sexual risk behaviors and perception of HIV risk of students in a predominantly African American commuter urban university in the Midwest. Methods Students enrolled in randomly selected general education courses completed a paper and pencil survey. Data were collected in Fall 2007, and univariate, bivariate, and multivariate analyses were conducted using SPSS for Windows v.16. Results The sample included 390 students, the majority (83%) of whom were never married and 87% were sexually experienced. Among males reporting male partnerships those who used marijuana (OR = 17.5, p = 0.01) and those who used alcohol along with illegal drugs (OR = 8.8, p = 0.03) were significantly more likely to report multiple partnerships. Among females reporting male partnerships, those 30 years and older were significantly less likely (OR = 0.09, p = 0.03) to report having multiple male partners. There were significant differences in condom use last sex (p = 0.01) and consistent condom use (p = 0.002) among the different age groups. Older students were less likely to report condom use. Females age 30 years and older (OR = 3.74, p = 0.05) and respondents age 2029 years (OR = 2.41, p = 0.03) were more likely to report inconsistent condom use than those below 20 years. Marijuana use was correlated with inconsistent condom use (p = 0.02) and alcohol with not using condom last sex among females. Perception of HIV risk was generally poor with 54% of those age 30 years and older, 48.1% of 2029 year olds, and 57.9% of those below the age of 20 years perceived themselves as not having any chance of being infected with HIV. Predictors of moderate/good perception of HIV risk were drug and alcohol use, inconsistent condom use, and multiple partnerships. Conclusion Students in the study sample engaged in various HIV risk behaviors but have a poor appreciation of their risk of HIV infection. While low rates of condom use was a problem among older students (30 years and older), multiple partnerships were more common among younger students, and marijuana and alcohol use were related to low condom use among females. Our findings support the need for targeted HIV prevention interventions on college campuses.